1991
DOI: 10.1021/bi00243a007
|View full text |Cite
|
Sign up to set email alerts
|

Formation of cyclobutane thymine dimers photosensitized by pyridopsoralens: quantitative and qualitative distribution within DNA

Abstract: As after irradiation with 254-nm UV light, exposure of thymidine and three isomeric pyridopsoralen derivatives to UVA radiation, in the dry state, leads to the formation of the six diastereomers of cyclobutadithymidine as the predominant reaction. This unexpected photosensitized reaction, which also gives rise to both 5R* and 5S* diastereomers of 5,6-dihydro-5-(alpha-thymidylyl)thymidine (or "spore" photoproduct), is selective since [2 + 2] dimerization of 2'-deoxycytidine was not detected under the same exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…There is an abundant literature on the TTET-mediated formation of CPDs in ds DNA by several photosensitizers, including acetone (142), acetophenone (54,142), benzophenone (54,143), carprofen (144), fenofibric acid (143), fluoroquinolones (92,93,145), ketoprofen (143) and three pyridopsoralen derivatives (146,147). The predominant CPD photoproduct of the latter photosensitized reactions was found to be cis-syn T<>T, in agreement with the fact that thymine exhibits the lowest triplet energy (E T ) among nucleobases (148).…”
Section: Triplet Energy Transfersupporting
confidence: 71%
“…There is an abundant literature on the TTET-mediated formation of CPDs in ds DNA by several photosensitizers, including acetone (142), acetophenone (54,142), benzophenone (54,143), carprofen (144), fenofibric acid (143), fluoroquinolones (92,93,145), ketoprofen (143) and three pyridopsoralen derivatives (146,147). The predominant CPD photoproduct of the latter photosensitized reactions was found to be cis-syn T<>T, in agreement with the fact that thymine exhibits the lowest triplet energy (E T ) among nucleobases (148).…”
Section: Triplet Energy Transfersupporting
confidence: 71%
“…[12] It is therefore concluded that both singlet and triplet excited states can contribute to CPD and SP formation, while only singlet excited states are responsible for 6-4PP formation.…”
Section: Discussionmentioning
confidence: 98%
“…[11] In the presence of pyridopsoralens as photosensitizer, UVA light can also induce SP formation, [12] suggesting that thymine triplet excited state is likely responsible for the SP photochemistry. [13] A recent computational study with dinucleotide TpT implies that the excitation of the 3'-T alone may be sufficient for the 6-4PP photochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…2) In D N A in vitro pyrimidine dimers are apparently induced concomitantly to MePyPs furan side photomonoadducts. 18 3) The two diastereoisomers of the MePyPs-thymidine monoadduct first characterized in D N A ~o l u t i o n '~ and in D N A isolated from treated yeast cells show slight differences in repair.20…”
Section: Introductionmentioning
confidence: 99%